PENGARUH KARAKTERISTIK KOMITE AUDIT DAN PERUSAHAAN TERHADAP KECURANGAN PELAPORAN KEUANGAN - Prasetyo, Andrian Budi (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2014)
This study aimed to examine the effect of audit committee and firm characteristics against thepossibility of fraudulent financial reporting. Audit committee characteristics examined by anindependent audit committee, audit committee financial expertise, audit committee meetingsand tenure of the audit committee. Then, firm characteristics examined its effect on financialreporting fraud is managerial ownership, corporate leverage, firm size and growth rate of thecompany. The research was conducted by quantitative methods using secondary data. Secondarydata comes from a list of cases Bapepam-LK and the company’s annual report listed on theIndonesian Stock Exchange. This research population is company listed on the Indonesian StockExchange, and then the samples were taken by purposive sampling with criteria non-financialcompany and have the required data in this study. At last, total sample are 40 companies, thatcomprised into 20 companies with commit fraud financial reporting and 20 companies withdid not commit fraud in financial reporting with the same industry and size of company assets.This study uses logistic regression statistical tools because the dependent variable was dummyvariable (non metric), while the independent variable was metric and non metric variable.Theresults showed that the characteristics of audit committees (audit committee financial expertiseand tenure of the audit committee) have a negative impact on financial reporting fraud, while thefirm characteristics (managerial ownership and firm size) has a positive influence on financialreporting fraud. Furthermore, the other firm characteristics (growth companies) negatively affectthe financial reporting fraud.